Answer: 16m^4−25
Step-by-step explanation:
(4m^2−5)(4m^2+5)
=(4m^2+−5)(4m^2+5)
=(4m^2)(4m^2)+(4m^2)(5)+(−5)(4m^2)+(−5)(5)
=16m^4+20m^2−20m^2−25
=16m^4−25
Answer:
$7.65
Step-by-step explanation:
step one:
The total bill was $45.
michelle pays 35% of the total bill
= 35/100*45
=0.35*45
=$15.75
lori pays 48% of the bill
= 48/100*45
=0.48*45
=$21.6
Therefore patti will pay
=45-15.75-21.6
=$7.65
In order to find out what 36x + 9 is equivalent to,, we must factor out 9 from the expression. Once we do this you will find that this expression is equivalent to 9(4x + 1),, or option E.
Next we will look at the expression 9(4x -1). In order for us to find out the equivalent to this expression,, we must first multiply each term in the parenthesis by 9.
9 × 4x - 9
Now calculate the product
36x - 9
This means that the equivalent for this expression is 36x - 9,, or option A.
Lastly,, we will look at the final expression given which is 4(9x + 2). The first step for finding the equivalent of this expression is to multiply the numbers in the first parenthesis together.
(36x) + (4 × 2)
Now multiply the numbers in the second parenthesis together.
(36x) + 8
Remove the parenthesis
36x + 8
Now factor out 4 from the expression to get your final answer.
4(9x + 2)
This means that the last expression is equivalent to 4(9x + 2),, or option C.
Let me know if you have any further questions
:)
Answer:
Reflection
Step-by-step explanation: It is reflection because it is the same thing just reflected
The slope will be -3/4
To find slope you just place the change in y over the change in x.
2- -1=3
0-4= -4
The slope is -3/4 which is the same as before